Ideologi Dalam Tafsir Al-Huda Tafsir Qur’an Basa Jawi Karya BRIGJEND (PURN.) DRS. H. Bakri Syahid - Kojin; Choliza, Suraya; Teguh, Muhammad; Saddad, Ahmad; Alva Fauziyah, Desriana (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This article focuses on one of the archipelago's tafsir books, namely tafsir al-Huda: Tafsir Qur'an Basa Jawi written by Bakri Syahid. A person who holds the rank of colonel and participates in the military and political world. Although his tafsir is not well known in the field of tafsir science, but this tafsir al-Huda has its own uniqueness among the interpretations of the archipelago in general. Tafsir al-Huda is heavily influenced by Bakri Syahid's military rank, academics and positions. Covering the background of interpretation, methods of interpretation, style of interpretation, flow of interpretation and references used in writing tafsir al-Huda. For the author of tafsir al-huda is a uniqueness in terms of the book of interpretation and the author who has a different background than the mufassir-mufassir in general. In terms of authorship, this tafsir also uses Javanese Latin which has its own uniqueness and specialty. Keywords: Tafsir, Nusantara, al-Huda